PWE-087 Interleukin-17a Homodimer Reduces Pro-inflammatory Cytokine Production By Inflammatory Bowel Disease Mucosa Cultured Ex Vivo. (9th June 2014) - Biancheri, P; Di Sabatino, A; Curciarello, R; Corazza, GR; Lindsay, JO; MacDonald, TT
Abstract : Introduction: Interleukin (IL)-17A, which is up-regulated in inflammatory bowel disease (IBD) mucosal lesions, and IL-17F are normally present as IL-17AA and IL-17FF homodimers and may occasionally form IL-17A/F heterodimers. The role of each IL-17 dimer in IBD is currently unknown. Therefore, we studied the effects of IL-17AA, IL-17FF and IL-17-A/F in ulcerative colitis (UC) and Crohn's disease (CD) mucosa. Methods: Inflamed colonic biopsies from 17 IBD patients (6 UC and 11 CD) were cultured ex vivo for 24 h with IL-17AA, IL-17FF or IL-17A/F (1 ng/ml). Mucosal myofibroblasts isolated from the inflamed colon of 4 CD and 4 UC patients were cultured for 24 h with tumour necrosis factor (TNF)-α 20 ng/ml or with increasing concentrations (1–100 ng/ml) of IL-17AA, IL-17FF or IL-17A/F. IL-6 and IL-8 were measured in culture supernatants by ELISA. Results: IL-17AA, but not IL-17FF, significantly reduced both IL-6 and IL-8 production by inflamed IBD biopsies cultured ex vivo, whereas IL-17A/F decreased IL-8 release by IBD mucosa. No difference was observed between CD and UC. Neither IL-17AA, nor IL-17FF, nor IL-17A/F exerted any effect on IL-6 and IL-8 production by IBD myofibroblasts. As expected, TNF-α stimulation significantly increased IL-6 and IL-8 production by both CD and UC myofibroblasts in vitro . No difference was observed between CD and UC myofibroblasts. Conclusion: IL-17AA exerts an anti-inflammatory action on inflamed IBD biopsies cultured ex vivo . The action of IL-17AA is not mediated by myofibroblasts, therefore further studies are underway to ascertain which cell type is the main target of IL-17AA in IBD mucosa. Disclosure of Interest: None Declared.